Awareness about diabetes mellitus and diabetic retinopathy in patients with diabetes mellitus - Sheth, Neeti R.; Sareshwala, Nabilah A.; Chaudhary, Sushil G.; Matai, Hiren D. (International Journal of Research in Medical Sciences, 2017)
Background: Awareness about diabetes mellitus and diabetic retinopathy in patients with diabetes mellitus. Methods: 50 patients of diabetes mellitus attending Pandit Deendayal Upadhyay Medical College, Rajkot, Gujarat, India, were randomly selected during January 2017 to March 2017. 11-point questionnaire obtained on detailed search of literature on published reports were administered by interviewers well versed in English and Gujarati. Results: Total of 50 patients were randomly selected.42%- females and 58% - males. Mean age - 58.5 years. Age range 40 to 71 years. Patients with good sugar control -26% and poor control - 74%. 94% of the patients were taking treatment for DM and 6% were not on any treatment. 48 % of the patients were illiterate, 10% were graduate and 42% had education below 12th standard. 50% were aware about DM affecting the eye .38% had taken eye treatment and 62% had not. 26% were aware of DM affecting eye inspite of good control and 26 % aware of the need of check-up in poor control. 40% aware of the complications related to DM. Conclusions: Better literacy rates is contributory to public awareness, however trend for poor practice needs to be radically changed with aggressive public motivation emphasizing the necessity of screening and follow ups.